EDUCATION 5.0: CHALLENGES AND PROSPECTS FOR ACADEMIC LIBRARIESWORKING FOR A BETTER TOMORROW ACCELERATING THE IMPLEMENTATION OF THE UN SUSTAINABLE DEVELOPMENT GOALS - Garcia-Fedo, Loida (Nazarbayev University, 2023)
Education 5.0: Challenges and Prospects for Academic Librariesworking for a better tomorrow accelerating the implementation of the UN Sustainable Development Goals
Keywords: Type of access: Open Access; Education 5.0; Academic Libraries; UN Sustainable Development Goals